THE TRAGEDY OF THE PERIOD IN THE STORIES OF ABDULLA KAKHHOR - Isayeva Shoira (Galaxy International Interdisciplinary Research Journal, 2021)
This article analyzes the ideological and artistic aspects of Abdullah Qahhor’s stories. In addition, attempts have been made to portray the tragedy of the period in the writer’s style and narratives.